EFFECTIVENESS OF NEEM LEAF EXTRACT (Azadirachta indica juss) IN KILLING COCKROACHES - Agus Widada; Citra Ayu Lestari1; Jubaidi; Rosalia Rina Bathari (Proceeding B-ICON, 2023)
Vectors are arthropods that can transmit, transfer or become a source of disease in humans. Efforts to control and eradicate disease need to be carried out to prevent disease transmission. One of these efforts is by using vegetable insecticides. The purpose of this study was to determine the effective concentration of neem leaves (Azadirachta indica juss) as an insecticide for dubia cockroaches. Research design is Quasi Experiment with Post-Test research design with Control design. Data analysis used One Way Anova test and Benferroni test. The results of the study using clove leaf extract with concentrations of 20%, 25%, and 30% were able to kill an average of 3.66 cockroaches (18.3), 6.67 (33.35%), 15.00 ( 75%), 20,000 heads (100%).The results of the One Way Anova test show the p value = 0.000 <0.05. This means that there are differences in the number of house fly deaths by presenting various concentrations of neem leaf extract in killing cockroaches. The percentage of cockroach deaths at a concentration of 20% was (58.35%), 25% was (16.33%), 30% was (100%). The most effective treatment in killing cockroaches (Blaptica Dubia). It is hoped that it can increase knowledge to the wider community about the benefits of neem leaf extract which can be used as a natural insecticide in the hope of controlling cockroaches independently